Leveraging ROTI map derived from Indonesian GNSS receiver network for advancing study of Equatorial Plasma Bubble in Southeast/East Asia - Prayitno Abadi; Ihsan N. Muafiry; Teguh N. Pratama; Angga Y. Putra; Suraina; Gatot H. Pramono; Sidik T. Wibowo; Febrylian F. Chabibi; Umar A. Ahmad; Wildan P. Tresna; Asnawi (Earth and Planetary Physics)
This paper highlights the crucial role of Indonesia’s GNSS receiver network in advancing Equatorial Plasma Bubble (EPB) studies in Southeast and East Asia, as ionospheric irregularities within EPB can disrupt GNSS signals and degrade positioning accuracy. Managed by the Indonesian Geospatial Information Agency (BIG), the Indonesia Continuously Operating Reference Station (Ina-CORS) network comprises over 300 GNSS receivers spanning equatorial to southern low-latitude regions. Ina-CORS is uniquely situated to monitor EPB generation, zonal drift, and dissipation across Southeast Asia. We provide a practical tool for EPB research, by sharing two-dimensional rate of Total Electron Content (TEC) change index (ROTI) derived from this network. We generate ROTI maps with a 10-minute resolution, and samples from May 2024 are publicly available for further scientific research. Two preliminary findings from the ROTI maps of Ina-CORS are noteworthy. First, the Ina-CORS ROTI maps reveal that the irregularities within a broader EPB structure persist longer, increasing the potential for these irregularities to migrate farther eastward. Second, we demonstrate that combined ROTI maps from Ina-CORS and GNSS receivers in East Asia and Australia can be used to monitor the development of ionospheric irregularities in Southeast and East Asia. We have demonstrated the combined ROTI maps to capture the development of ionospheric irregularities in the Southeast/East Asian sector during the G5 Geomagnetic Storm on May 11, 2024. We observed simultaneous ionospheric irregularities in Japan and Australia, respectively propagating northwestward and southwestward, before midnight, whereas Southeast Asia’s equatorial and low-latitude regions exhibited irregularities post-midnight. By sharing ROTI maps from Indonesia and integrating them with regional GNSS networks, researchers can conduct comprehensive EPB studies, enhancing the understanding of EPB behavior across Southeast and East Asia and contributing significantly to ionospheric research.